Women and Social Justice: Some Legal and Social Issues in Contemporary Muslim Society By Anis Ahmad. Islamabad: Institute of Policy Studies, 1991, 128pp (American Journal of Islam and Society, 1991)
The task undertaken in this book, the development of a “third approach”to the issue of women’s oppression superceding both feminism and traditionalism,is much needed and much neglected in the Islamic movement.Specifically, Ahmad analyzes the impact of the introduction of hudud (Islamicpenal code) laws in Pakistan and makes policy recommendations for theirreform. Although his analysis is not limited in usefulness to Pakistan, it islimited, however, by several shortcomings in argument, structure, and language.Ahmad’s strong points emerge in his empirical study of Pakistani familylaw. While he attempts to refute the criticism that the hudud laws discriminateagainst women, he also recognizes that the application of these laws in alegal patchwork fraught with contradictions has not helped women. For example,the Family Laws Ordinance of 1961 requires all marriages to be officiallyreported but, with common and Islamic opinion being contrary, thislaw is frequently neglected. So when the hudud laws of 1979 made adulterypunishable, women living in Islamic but unreported marriages were reportedfor adultery by vengeful ex-husbands. This particular problem would be solved,Ahmad argues, by punishing such men for slander, a neglected aspect ofthe Shari‘ah’s approach to adultery which is to women’s advantage. He arguesfor an end to “this vicious circle of immediacy, adhocism and temporarysolutions” (p. 48) in the application of the Shari‘ah, and for a more creative,comprehensive reform. His use of statistics from Pakistani courts is an attemptto ground his analysis in the living reality of Pakistani women, anattempt which is only infrequently made by Islamist writers on women’s issues,who usually hide behind obscure generalizations about the ideal society.It is also edifying to see an Islamist writer admit that “we should notdoubt the intent and motive of those who talk on these issues and take adifferent position” (p. 11). Too often this debate over the status of womenresults in bitter and useless finger-pointing in which the advocates of changein women’s conditions are labelled “Western,” as if one had to be Westernto see anything exploitative about the present treatment of Muslim women.Unfortunately, Ahmad does not stick to his promise and succumbs to a defensivediatribe against his ideological opponents, calling them ‘‘crypto-colonialists’’and emphasizing their emergence from the upper classes. The same charge ...